Platycodon D-induced A549 Cell Apoptosis through RRM1-Regulated p53/VEGF/ MMP2 Pathway - Li, Jiurong; Ma, Aiping; Lan, Wenbin; Liu, Qun (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: Lung cancer is one of the leading causes of cancer-related deaths worldwide. Platycodin D (PD), a major pharmacological constituent from the Chinese medicinal herb named Platycodonis Radix, has shown potent anti-tumor activity. Also, it is reported that PD could inhibit cellular growth in the non-small-cell lung carcinoma (NSCLC) A549 cell line. However, the underlying mechanism is not fully clarified. Methods: Cell proliferation was measured by MTT assay. Annexin V and propidium iodide (PI) assay were employed to study the apoptosis effects of PD on A549 cells. Western blot analysis was used to evaluate protein expression. Also, we used a siRNA against p53, as well as a plasmid-based RRM1 over-expression to investigate their functions. Results: It is demonstrated that PD inhibited A549 cell proliferation in a dose- and time-dependent manner. Further investigations showed that PD induced cell apoptosis, which was supported by dose-dependent and time-dependent caspase-3 activation and p53/VEGF/MMP2 pathway regulation. Also, PD demonstrated the inhibition effect of ribonucleotide reductase M1 (RRM1), whose role in various tumors is contradictory. Remarkably, in this work, RRM1 overexpression in A549 cells could have a negative impact on the regulation of the p53/VEGF/MMP2 pathway induced by PD treatment. Note that RRM1 overexpression also attenuated cell apoptosis and inhibition of cell proliferation of A549 treated with PD. Conclusion: The results suggested that PD could inhibit A549 cell proliferation and induce cell apoptosis by regulating p53/VEGF/MMP2 pathway, in which RRM1 plays an important role directly.
Keywords: platycodin D